Japan-U.S. Real Exchange Rate Behaviour: Evidence from Linear and Non-Linear Endogenous Break Tests - Chan Tze-Haw; Chong Lee-Lee; Hooy Chee-Wooi (Asian Academy of Management Journal of Accounting and Finance, 2011)
This paper explores the mean reversion behaviour of three Japanese real exchange rates during January 1980–January 2010. The CPI- and PPI-based real yen/USD rates and real effective yen rates are examined using newly improved unit root tests allowing for endogenous break(s) in the linear and non-linear manner. We identify structural breaks in 1985 and 1997/98, respectively, via the linear tests from Zivot and Andrews (1992) and Lumsdaine and Papell (1997), but the results were mostly against the PPP hypothesis. The test from Saikkonen and Lütkepohl (2002), however, provides sufficient support for the non-linear adjustment of real exchange rates towards long-run PPP (purchasing power parity), which suggests the goods market integration between the two nations. The exchange rate misalignment is somewhat less evident after the Plaza Accord 1985, and stronger evidence for PPP is found in the post-1999 period. This is supported by a smaller persistency of real exchange (half-life < a year) found in sub-sample analysis. In brief, our findings reveal that the Japanese authorities have implemented a PPP-oriented rule as a basis for their exchange rate policies in the presence of structural break(s) and non-linearity.